Scl isoforms act downstream of etsrp to specify angioblasts and definitive hematopoietic stem cells - Ren, Xi (American Society of Hematology, 2010)
Recent lineage studies suggest that hematopoietic stem cells (HSCs) may be derived from endothelial cells. However, the genetic hierarchy governing the emergence of HSCs remains elusive. We report here that zebrafish ets1-related protein (etsrp), which is essential for vascular endothelial development, also plays a critical role in the initiation of definitive hematopoiesis by controlling the expression of 2 stem cell leukemia (scl) isoforms (scl-α and scl-β) in angioblasts. In etsrp morphants, which are deficient in endothelial and HSC development, scl-α alone partially rescues angioblast specification, arterial-venous differentiation, and the expression of HSC markers, runx1 and c-myb, whereas scl-β requires angioblast rescue by fli1a to restore runx1 expression. Interestingly, when vascular endothelial growth factor (Vegf) signaling is inhibited, HSC marker expression can still be restored by scl-α in etsrp morphants, whereas the rescue of arterial ephrinb2a expression is blocked. Furthermore, both scl isoforms partially rescue runx1 but not ephrinb2a expression in embryos deficient in Vegf signaling. Our data suggest that downstream of etsrp, scl-α and fli1a specify the angioblasts, whereas scl-β further initiates HSC specification from this angioblast population, and that Vegf signaling acts upstream of scl-β during definitive hematopoiesis.